Analysis of Arabic Subtitle Translation Techniques to Indonesian on Short Films Instagram Account @arabiyahtalks - Muhammad Arifin Ilham; Majid, Abdul; Supriadi, Rinaldi; Al Farisi, Mohammad Zaka (Assuthur: Jurnal Pendidikan Bahasa Arab, 2025)
In today's digital era, audiovisual content on social media is increasingly used to convey cross-cultural and linguistic messages. This research is motivated by the widespread use of subtitles as a communication bridge between languages, especially in religious and motivational content on social media. This study analyzed the subtitle translation technique from Arabic to Indonesian used in short films on @arabiyahtalks's Instagram account. This study uses a descriptive qualitative method with a case study approach. Data were obtained through video content documentation accompanied by Arabic-Indonesian subtitles, which were then analyzed to identify the translation techniques applied. The techniques found include reduction, amplification, transposition, and modulation. The results show that these techniques effectively bridge the linguistic and cultural differences between Arabic and Indonesian. Translators can convey spiritual and emotional messages in their entirety without losing their original nuances, thus creating translations that are easy to understand and relevant to Indonesian audiences. The conclusion of this study emphasizes the importance of applying appropriate translation techniques in the digital context to ensure the message's accuracy while maintaining language flexibility. The main contribution of this research lies in expanding the study of social media translation and providing practical guidance for digital content translators to be more sensitive to the cultural and emotional context of the target audience.